How did A V Hill understand the VO2max and the "plateau phenomenon"? Still no clarity? - Noakes, T. D. (British Journal of Sports Medicine, 2008)
Objectives: A recent editorial in Medicine and Science in Sports and Exercise concludes that the study of Hawkins and colleagues confirms "beyond any doubt the proposition of Hill and Lupton". It is not clear which of Hill and Lupton`s propositions have been proved "beyond any doubt".